2008
DOI: 10.1038/cr.2008.296
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel sense and antisense transcription at the TRPM2 locus in cancer

Abstract: It has been proposed that in cancer, where the bulk of the genome becomes hypomethylated, there is an increase in transcriptional noise that might lead to the generation of antisense transcripts that could affect the function of key oncosuppressor genes, ultimately leading to malignant transformation. Here, we describe the computational identification of a melanoma-enriched antisense transcript, TRPM2-AS, mapped within the locus of TRPM2, an ion channel capable of mediating susceptibility to cell death. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 35 publications
2
110
0
1
Order By: Relevance
“…We anticipate this TRPM2 nuclear translocation is a more general phenomenon as we also have observed it in other types of cancer cells (data not shown). It has been reported that two fragments (sense and antisense transcriptions) of TRPM2 are specifically expressed in cancer cells, 3 as our PCR and antibody targeted the C-terminus (exons 30-32, exon 25, respectively) it will be very interesting to see if the nuclear expressed TRPM2 represent or include the TRPM2 fragment of the sense transcription. If so, the cancerspecific transcription will create two functionally important fragment proteins-the antisense fragments inhibit the normal Ca 2 þ transport function of TRPM2 and the sense fragment conducts enzymatic function in the nucleus simultaneously.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We anticipate this TRPM2 nuclear translocation is a more general phenomenon as we also have observed it in other types of cancer cells (data not shown). It has been reported that two fragments (sense and antisense transcriptions) of TRPM2 are specifically expressed in cancer cells, 3 as our PCR and antibody targeted the C-terminus (exons 30-32, exon 25, respectively) it will be very interesting to see if the nuclear expressed TRPM2 represent or include the TRPM2 fragment of the sense transcription. If so, the cancerspecific transcription will create two functionally important fragment proteins-the antisense fragments inhibit the normal Ca 2 þ transport function of TRPM2 and the sense fragment conducts enzymatic function in the nucleus simultaneously.…”
Section: Discussionmentioning
confidence: 97%
“…1 The function of TRPM2 in cancer cells has recently been investigated. 2,3 Using a cDNA array technique, significantly increased TRPM2 mRNA expression has been observed in prostate cancer tissues and cell lines in comparison with normal prostate tissues (http:/ /www.ncbi.nlm.nih.gov/projects/geo/gds).…”
Section: Introductionmentioning
confidence: 99%
“…Four of these 5 genes have been reported in cancer or have been implicated in cell adhesion and metastasis. TRPM2 is a calcium channel activated by oxidative stress that regulates susceptibility to cell death (30 -33 ) and has been implicated in prostate cancer (32 ) and melanoma (33 ). In a recent report by Orfanelli et al on aberrant sense and antisense transcripts derived from global hypomethylation studies in melanoma, several transcripts within the TRPM2 locus were enriched in melanoma (33 ).…”
Section: Discussionmentioning
confidence: 99%
“…TRPM2 mRNA was found in many primary breast tumors, but no apparent relationship to survival [51]. Besides, overexpression of TRPM2 increased susceptibility of melanoma to apoptosis [52]. Based on these conclusions, we speculate TRPM2 may play a critical role in the metastasis of OS.…”
Section: Discussionmentioning
confidence: 82%